WACANA STAND UP COMEDY PRANCIS DAN INDONESIA TINJAUAN KOHESI DAN KOHERENSI - , ESA AGITA ANJANI; , Drs. B.R Suryo Baskoro, MS. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Stand up comedy, that is comedy considered as a smart comedy,is an art comedy show which develops rapidly in all over world nowadays.. This research will concern about french and indonesian stand up comedy discourse by French comedians Gad Elmaleh and Tomer Sisleyand Indonesian comedians Raditya Dika and Jui Purwoto. This paper focus on cohesion and coherence analysis. The results showed that cohesion and coherence are the most important aspect for making a good stand up comedy discourse. Cohesion aspects in the data are gramatical cohesion (reference, substitution, ellipsis, conjunction) and lexical cohesion (repetion, synonim, antonym, collocation). And coherence aspects consist of additional relation, temporal relation, oppositional relation, affectional relation, causal relation, conditional relation, etc.